EFEKTIFITAS TEKNIK RELAKSASI NAFAS DALAM DAN TEKNIK RELAKSASI GENGGAM JARI TERHADAP PENURUNAN NYERI PADA PASIEN POST OPERASI APENDIKSITIS DI RUMAH SAKIT MOJOKERTO - Arif Hidayat; Ike Prafita Sari; Kartiningrum, Eka Diah (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Appendicities is the most common of infection at apendiks vermiformis. In patient after surgery. that caused by surgical inflammation of the wound. Non-pharmacological nursing actions can reduce pain by deep breath relaxation and finger held relaxation technigues. this study aimed to investigate the effectiveness of inner breath relaxation techniques and finger held relaxation techniques on pain reduction in post-appendicitis patients in the Sidowaras Hospital at Hayam wuruk room. This research used Quasy Experiment with pre test and post test one group design. The number of research samples are 24 respondents by using Accidintal Sampling. Data analyzed in this research by using Wilcoxon sign rank test.showed In the respiratory relaxation intervention group obtained ρ value ( 0.003) obtained and in the finger held relaxation. relaxation intervention group obtained p value ( 0.005) U Mann Withney test showed the effectiveness of both groups got p value ( 0.949) which means there is no effectiveness between deep breathing relaxation techniques and handheld relaxation techniques finger. Both of these techniques can be done post-operative patients appendicitis to be selected without distinguishing the effectiveness of both. Patient can choose one of the techniques for restoring her health